New bipolar host materials using Phenanthro[9, 10-d]oxazole moiety for highly efficient red phosphorescence. (March 2020) - Kang, Seokwoo; Park, So-Ra; Suh, Min Chul; Park, Jongwook
Abstract: Six new bipolar host materials including phenanthro[9, 10- d ]oxazole as an electron withdrawing unit and three different amine groups as electron donating units have been designed and synthesized for use in red phosphorescent organic light-emitting diodes (PhOLEDs). The synthesized materials showed PLmax at 397–455 nm and high thermal properties above the decomposition temperature (Td ) of 320 °C. In addition, all six materials showed distinct oxidation-redox peaks as bipolar materials. These six new bipolar host materials are suitable for use in red PhOLEDs due to their triplet energy level (e.g., 2.2–2.5 eV). As a result, when the six new materials were used as host materials for red PhOLEDs, 24.0–29.4 cd/A maximum current efficiency, 16.5–19.3% external quantum efficiency, CIE (0.64, 0.35), and 610 nm ELmax were achieved. Graphical abstract: Image 1 Highlights: Bipolar host materials through different donors and acceptor of phenanthro[9, 10- d ]oxazole were synthesized. Six new bipolar host materials are suitable for use in red PhOLEDs. In case of the o -OPDP device, the EQE of 19.3% was achieved.